MENINGKATKAN KEMAMPUAN BERBICARA MELALUI PERMAINAN PESAN BERANTAI PADA ANAK USIA DINI DI TK RIAN KUMARAJAYA - Hilda Widyanti; Erni Nurul Romlah; Ade Sadikin Akhyadi; Dedah Jumiatin (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Speaking skills are very important for an early child. The ability to speak isa verbal form of communication that is used to communicate smoothly So that other people can understand what children are up to.But most early children still have trouble speaking.Many of the factors behind it, one of which is the lack of creativity of the suspended teacher to provide The stimulus in children is applying an attractive learning method for early childhood.One method of learning that can be used is the method of chain message play.It USES a class action research method with a model of the kemmis and tagart cycles. Research subject is child group b 15 of them. Based on a pediatric research with the structure of infant speech 13%, cycle I 27% and cycle ii 66%. From the data gained it could be referenced that child's speech level can be improved through a chain message game.may add a full count of the child’s vovabulary from information received in sentences or words,so that the child’s speaking skills can be trained and can communicate with the environment. So the ability to talk a child can improved.